Photovoltaic efficiency enhancement via magnetism - Verma, Monika; Gautam, Sanjeev (Journal of magnetism and magnetic materials, 2023)
The efficiency of photovoltaic cells has long been a subject of intense concern and research. Diverse photovoltaic cell types have been developed, including crystalline silicon cells (achieving up to 27.6% efficiency), multijunction cells (reaching up to 47.4% efficiency), thin film cells (attaining up to 23.6% efficiency), and emerging photovoltaic cells (exhibiting up to 33.7% efficiency). Despite advancements, achieving high efficiency on an industrial scale remains a significant challenge due to factors like charge carrier recombination rate, defects, and the temperature’s influence. Numerous approaches have been explored to address these challenges, encompassing strategies such as incorporation of nanoparticle within the active layer, studying transport properties and defects using ion beams, utilizing magnetite materials, and leveraging the application of magnetic fields. The influence of a magnetic field can amplify the generation of charge transfer states exhibiting triplet characteristics, increasing the charge separation time. However, magnetic fields introduce spin-based effects, enabling the investigation of interactions between electron spins and magnetic fields through state-of-an-art synchrotron radiation techniques like XMCD. Several innovative cell configurations have reported substantial efficiency enhancements under the influence of magnetic fields. Examples include TiO2-BiFeO3 dye-sensitized cells, polymer-based cells with Fe3O4@PANI additives integrated into TiO2-based dye-sensitized cells, and the incorporation of Fe-doped SnO2 within the active layer of heterojunction organic solar cells. In this perspective review, the profound impact of magnetism on enhancing efficiency in photovoltaic cells has been analyzed and the utilization of advanced X-ray absorption spectroscopic techniques to probe and comprehend these intricate effects. [Display omitted] •Energy harvesting technique from solar energy using photovoltaics.•Power conversion efficiency (PCE) of various PVs and influencing factors.•Magnetism to enhance efficiency by amplifying triplet states within PV cells.•Atomic and bulk magnetic measurements comparison & industrial applications.